2022
DOI: 10.1097/ncc.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Language Features Associated With Needs of Ovarian Cancer Patients and Caregivers Using Social Media

Abstract: BackgroundOnline health communities (OHCs) can be a source for clinicians to learn the needs of cancer patients and caregivers. Ovarian cancer (OvCa) patients and caregivers deal with a wide range of unmet needs, many of which are expressed in OHCs. An automated need classification model could help clinicians more easily understand and prioritize information available in the OHCs.ObjectiveThe aim of this study was to use initial OHC postings to develop an automated model for the classification of OvCa patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Fourth, these platforms provide cancer patients medical information allowing to reduce their distress (Bender et al, 2021). Fifth, using social media allows patients to share medical and personal information with their doctors and nurses (Lee et al, 2021). Sixth, thanks to social media, patients better understand hospitals' internal functioning, which helps them to participate in medical procedures in a more efficient way (Guan et al, 2021).…”
Section: Cancer Hospitals' Corporate Communication Strategiesmentioning
confidence: 99%
“…Fourth, these platforms provide cancer patients medical information allowing to reduce their distress (Bender et al, 2021). Fifth, using social media allows patients to share medical and personal information with their doctors and nurses (Lee et al, 2021). Sixth, thanks to social media, patients better understand hospitals' internal functioning, which helps them to participate in medical procedures in a more efficient way (Guan et al, 2021).…”
Section: Cancer Hospitals' Corporate Communication Strategiesmentioning
confidence: 99%
“…We used logistic regression with bagof-word features for this task as it is a simple and interpretable classifier. Moreover, it has shown promising results in recent work on predicting patient needs from social media conversations, with limited training data [23,27]. We involved healthcare professionals and medical students for annotating 5K conversations to train the classifiers.…”
Section: Data Modelmentioning
confidence: 99%
“…Considering the massive number of online sources that may contain ADRD caregiving discussions, it is crucial for researchers to develop machine learning algorithms that can efficiently identify the relationship between caregivers and persons living with dementia based on their online posts, which will be a valuable social determinant that can be applied to online social support-based research. Various machine learning algorithms have been developed to extract relevant information from massive, noisy online data to facilitate biomedical research [ 36 ], including, but not limited to, predicting mental health status [ 37 ], disseminating study information during the COVID-19 pandemic [ 38 ], and learning the needs of patients with ovarian cancer and their caregivers [ 39 ]. However, most studies in the ADRD caregiving field have either identified online ADRD caregiving discussions [ 26 ] or summarized caregiving challenges [ 35 ].…”
Section: Introductionmentioning
confidence: 99%